Arrangement of blood vessels in the wall of jaw cysts - YOKOBAYASHI, Yasuo (Japanese Journal of Oral and Maxillofacial Surgery, 1990)
The arrangement of blood vessels in the cyst wall was studied in 10 radicular cysts, 10 old radicular cysts, 5 non-keratinizing primordial cysts, 5 odontogenic keratocysts, 5 dentigerous cysts and 5 nasopalatine duct cysts. The majority of blood vessels in the cyst wall were consisted of capillaries (68.8%) and venules (25.3%) and there was no statistical difference in the distribution of constituent vessels between inflammatory cysts and developmental cysts. The deepest layer of the cyst wall showed the highest incidence of inflammation which decreased gradually towards the outer layer in both inflammatory and developmental cysts. However this tendency was more conspicuous in inflammatory cysts and there was no section in which histological evidence of inflammation was not noted in the deepest layer of the inflammatory cysts. In both groups of cysts, the number of capillaries increased in a similar degree in the presence of inflammation. Furthermore, there was no difference in the number of blood vessels among different layers between the two cyst types when inflammation was present. Blood vessels were distributed more densely in the inner layer of the developmental cysts in sections with no evidence of inflammatory response, but this was not the case in the inflammatory cysts. When blood vessels in the cyst wall were divided into vertical and horizontal types by the angle made to the lining epithelium, the vertical type blood vessels increased in the presence of inflammation. The basic pattern of vascular arrangement in the inflammatory cysts was the predominance of vertical type in the deepest layer and horizontal type in the superficial layer. Despite the increase in the ratio of horizontal blood vessels, vertical type predominance was maintained even after inflammation subsided in the deepest layer. On the other hand, the cyst wall of the developmental cysts was consisted mainly of horizontal type blood vessels. In the presence of inflammation, the vertical type increased, but the horizontal type still predominanted in the deepest layer, whereas in the superficial layer the vertical type surpassed the horizontal type in most cysts. The results indicate that analysis of vascular arrangement in the cyst wall may be of help in the differential diagnosis of inflammatory cysts and developmental cysts.